Hubungan Antara Kepercayaan Diri Dengan Hasil Belajar Life Skill Mata Pelajaran Tata Rias Wajah Pada Siswa Kelas VII SMPN 138 Terbuka Cakung 3 Jakarta - Novia Sagita; Sri Irta Widjajanti; Neneng Siti Silfi Ambarwati (Journal on Education, 2024)
This research aims to determine the relationship between self-confidence and learning outcomes in the life skills course of facial makeup at SMPN 138 Terbuka Cakung 3 Jakarta. This research utilizes a quantitative method with a correlational design. The population consists of 32 seventh-grade students at SMPN 138 Terbuka Cakung 3 Jakarta, with the sample selected using Total Sampling, meaning the sample size equals the population. Data collection was conducted using questionnaires to measure self-confidence and secondary data to assess the learning outcomes in the life skills course of facial makeup. The data were analyzed using the Pearson Product Moment correlation coefficient test with the aid of SPSS software. The results indicate a significant relationship between self-confidence and student learning outcomes, with a correlation coefficient of 0,366 and a p-value of 0,165 (p > 0,05). The majority of students have self-confidence in the moderate category, with an interval of 103-111 and a percentage of 41%, while the learning outcomes fall within the interval of 67-75 with 44% also in the moderate category. The conclusion of this study is that self-confidence plays a significant role in enhancing students' learning outcomes. Therefore, educators are encouraged to pay more attention to factors that can boost students' self-confidence to achieve better learning outcomes. Further research is recommended to explore other factors that may influence students' learning outcomes.